Burnout Syndrome in Chilean Midwifery Students - Lopez-Alegria, F (SAGE Publications Inc., 2020)
The student Burnout Syndrome is a response to chronic and severe stress linked to the role of the students and their academic context. This study aims at determining the prevalence and severity of the student Burnout Syndrome on a sample of midwifery students and its associated factors. The study is observational, cross-sectional, and analytical, with a sample of 140 students of a Chilean university. The study variables were as follows: sociodemographic background, academic profile, student Burnout Syndrome scale, and behaviors in everyday psychosocial activities. The instrument for measuring the Burnout Syndrome was the Unidimensional Scale of Student Burnout. For the analysis, descriptive statistics were used, and the association of the independent over the dependent variables was assessed through linear regression. Of the third-year students, 77.2% had a moderate or deep burnout level, which increases to 91.8% in the fourth-year students. A significant and direct association was found between the syndrome and the career year. A significant association was also found between the Burnout Scale and the scale of psychosocial risk behavior. All the students present some degree of Burnout Syndrome, which is related to both their studies and psychosocial risks. © The Author(s) 2020.